PERKEMBANGAN DAN MODERNISASI AWAL PENDIDIKAN ISLAM DI TURKI UTSMANI DAN ANDALUSIA: TINJAUAN HISTORIS - Andesta, Rena; Aryati, Azizah; Mindani, Mindani; Putra Pratama, Nanda Jaka; Erawati, Tika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the early development and modernization of Islamic education in the Ottoman Empire and Andalusia, focusing on educational institutions, curricula, teaching methods, and socio-political contexts. Islamic education in both regions displayed diverse practices through formal institutions such as madrasahs, Rüşdye Mektebi, ribāṭ, and informal settings like mosques and tekkes. The research employs a descriptive qualitative method with literature and historical document analysis, including primary sources such as Evliya Çelebi’s Seyahatname and biographical accounts of intellectuals like al-Yuḥānisī, and secondary sources comprising scholarly articles and books on classical Islamic education. Findings indicate that the Ottoman education system emphasized structured curricula and early modern schools, while Andalusian education integrated religious and rational sciences with experiential learning such as riḥla (educational travel). Both regions benefited from financial support (waqf), social stability, and the role of intellectuals, although access for women and marginalized groups remained limited. The study underscores the relevance of classical Islamic educational models for contemporary education, highlighting the integration of formal and non-formal learning, multidiscipline curricula, and attention to socio-economic factors. These findings offer insights for modern Islamic educational practices aiming for holistic, inclusive, and contextual learning experiences.